2021
DOI: 10.3389/fmed.2021.778330
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Optical Coherence Tomography Angiography in Systemic Hypertension: A Meta-Analysis

Abstract: Objective: Multiple studies have compared various optical coherence tomography angiography (OCTA) parameters in participants with systemic hypertension vs. controls and have presented discordant findings. We conducted a meta-analysis to pool together data from different studies to generate an overall effect size and find out whether OCTA parameter(s) significantly differed in participants with systemic hypertension as compared to controls.Methods: We conducted a literature search through a search of electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Meta-analysis of 11 studies comparing selected OCTA parameters in the group of HT patients showed that eyes of HT individuals have lower superficial and deep vascular densities at the macula in comparison with healthy patients. The authors also indicated that OCTA was a useful tool in microcirculation assessment in HT patients [48]. The changes observed in eye microcirculation are consistent then with those observed in skin microcirculation of HT patients -in both cases it results in capillary rarefaction.…”
Section: Optical Coherence Tomography (Oct)supporting
confidence: 56%
“…Meta-analysis of 11 studies comparing selected OCTA parameters in the group of HT patients showed that eyes of HT individuals have lower superficial and deep vascular densities at the macula in comparison with healthy patients. The authors also indicated that OCTA was a useful tool in microcirculation assessment in HT patients [48]. The changes observed in eye microcirculation are consistent then with those observed in skin microcirculation of HT patients -in both cases it results in capillary rarefaction.…”
Section: Optical Coherence Tomography (Oct)supporting
confidence: 56%
“…The OCTA is also highly attractive for use in large cohort studies and for consecutive follow-up visits as it does not require the administration of intravenous dye 42 . A recent meta-analysis by our group reviewed the studies on quantitative OCTA parameters in hypertensive patients and concluded that certain OCTA parameters could provide objective information about preclinical microvascular changes from systemic hypertension 43 …”
Section: Optical Coherence Tomography Angiographymentioning
confidence: 99%
“…42 A recent meta-analysis by our group reviewed the studies on quantitative OCTA parameters in hypertensive patients and concluded that certain OCTA parameters could provide objective information about preclinical microvascular changes from systemic hypertension. 43…”
Section: Optical Coherence Tomography Angiographymentioning
confidence: 99%
“…However, first of all, we should consider some technical limits of OCT-A whereby a slow blood flow above a minimum threshold detected by the machine may be wrongly reflected as a vascular rarefaction or even an area of non-perfusion on OCT-A images [37], and some optical parameters, such as the axial length of the eye, and in particular myopic condition, that could induce noise in the image, making the vascular network appear artificially denser because of the larger area being scanned under smaller magnification [38]. Furthermore, the results of 11 studies on macular vessels rarefaction reported in a recent meta-analysis [39] should be analyzed considering the Asiatic ethnicity of most of the study populations (9 out of 11 studies considered Asiatic populations) [8,10,11,34,[40][41][42][43][44], and the inclusion of patients with hypertensive retinopathy in the study groups [10,44].…”
Section: Discussionmentioning
confidence: 99%